PREJUDICE AND BULLYING IN HIGHER EDUCATION: AGE AS AN ANALYSIS VARIABLE - Galuch, Maria Terezinha Bellanda; Gilioli, Eduardo Borba; Sanches, Eduardo Oliveira; Ribas, Haira Lima; Czyżewski , Analice (Seven Editora, 2024)
This research aimed to verify possible relationships between age and personality characteristics, such as sadomasochism, fragility of the Self and narcissism, and between age and the type of violence manifested by higher education students throughout their school life. The sample, composed of 172 academics from 12 undergraduate courses from public and private institutions based in the northwest of Paraná, was applied the following research instruments: a division of the Fascism Scale into: Scale F of sadomasochism and Scale F of Fragility of the Self; Narcissistic characteristics scale; Scale of manifestation of prejudice, divided into the following targets: ethnicities, people with disabilities, LGBTQIA+; Moral Prejudice Scale; Bullying Scale and Bullying Target Scale. The results indicate that the increase in age is positively related to fascist behavior, prejudice against people with disabilities, against minority groups and against LGBTQIA+ people. DOI:https://doi.org/10.56238/sevened2024.037-061